Precarious Professionals: Layoffs and Gender Inequality in the Oil and Gas Industry. (12th January 2022) - Bosky, Amanda; Muller, Chandra; Williams, Christine L
Abstract: As mass layoffs, downsizing, and corporate restructuring have become standard organizational practices, professional work is becoming less stable. We examine the effects of this turbulence on gender inequality through a case study of layoffs in the oil and gas industry. Using a longitudinal survey that followed a cohort of recently hired scientists and engineers at a multinational oil and gas company from 2012–2016, we find that a major reduction-in-force during our study resulted in significant gender disparities in firm departures. Results indicate that about seventy percent of the gender gap in departures can be explained by underlying gender differences in the formal layoff criteria and workers' experiences in the firm prior to layoffs, pointing to formal organizational processes as insidious mechanisms driving inequality. The firm stated that layoffs were determined by performance and skill set, but the actual attributes for surviving layoffs turned out to be more malleable and open to bias. Results suggest that the firm's performance rating system may provide a pathway through which women's relational disadvantages became formalized in seemingly bureaucratically neutral ways. Our findings illustrate how increasing insecurity in professional careers may disadvantage women and shed light on the organizational mechanisms that reproduce gender inequality in professional work today.